A giant Condyloma Acuminata of Buschke and Lowenstein extending to the inguinal area and penis - Gafur Khairli; Anvar Davranov; Akylbek Zhumakayev; Yernur Ainayev; Ulanbek Balpukov; Asset Bolatov; Elijah Kehinde (National Scientific Medical Center, 2018)
Objective: Anogenital warts (condyloma acuminatum or veneral warts) are a common sexually transmitted disease among males and females. The causal role of human papilloma virus in anogenital wart formation has been firmly established. Case presentation: We report a case of a giant condyloma acuminata involving the penis, inguinoscrotal area and extending to the pubic region in a 30-year-old male patient. It was treated by wide surgical excision. Excision defect was extensive and required cover with fascio-cutaneous flap. The postoperative course of the patient was uneventful. Histological examination confirmed giant condyloma acuminata without evidence of malignancy. Conclusion: While there is no standard treatment for giant condyloma acuminate due to its biological behavior, surgical excision remains the method of choice to achieve local control of the disease. This case report confirms previous observation that extensive giant condyloma acuminate involving the penis or groin areas rarely become malignant compared to that involving the anorectal area of the body.